Total Porosity of Tight Rocks: A Welcome to the Heat Transfer Technique - Roshan, H.; Sari, M.; Arandiyan, H.; Hu, Y.; Mostaghimi, P.; Sarmadivaleh, Mohammad; Masoumi, H.; Veveakis, M.; Iglauer, Stefan; Regenauer-Lieb, K. (American Chemical Society, 2016)
Total rock porosity is a key parameter in a wide range of disciplines from petroleum to civil and mining engineering. Porosity is particularly important in petroleum engineering applications, e.g., from estimation of hydrocarbon in place to prediction of geomechanical properties. Conventional techniques used to measure the total porosity, i.e., mercury intrusion, nitrogen physisorption, focused ion beam–scanning electron microscopy (FIB–SEM), nuclear magnetic resonance (NMR) spectroscopy, gas porosimetry, and X-ray micro-/nano-computed tomography (micro-CT), have yielded inconsistent results for unconventional shale gas samples. A new robust yet practical method is thus required for measuring total porosity in tight formations to be added to the toolbox of the porosity measurement. We propose and develop here a new technique using the concept of heat transfer in porous media. This new heat technique route (HTR) was tested on a highly homogeneous Gosford sandstone benchmark to evaluate its reliability and repeatability in estimation of the total porosity. An excellent agreement was found with the conventional mercury intrusion, gas porosimetry, and micro-CT imaging techniques. Subsequently, the total porosity of an organic-rich shale sample was measured using the HRT method and compared to the conventional techniques of nitrogen physisorption–mercury intrusion and FIB–SEM techniques. Finally, a Monte Carlo analysis was performed on heat transfer measurements, proving its robustness for total porosity measurements.